Refined and industrial salt - Ballesfin, Elpha R. (College of Engineering, 1964)
Crude, industrial, and refined iodized salt of less than 90%, 96.0% and 99.5% NaCl respectively is manufactured from sea water by combined solar and vacuum pan evaporation. Precipitations of calcium and magnesium, carbonates are effected by treatment with caustic soda and carbon dioxide gas. The economic survey suggests the great need for putting up a plant to meet the local demand as far as quantity and quality are concerned. The processes recommended are discussed and the report includes process and equipment design and the economics involved. Results show the feasibility of putting up the plant in the country.